Communicating climate change and energy security : new methods in understanding audiences - Philo, Greg; Happer, Catherine (New York ; London : Routledge, 2013)
"This book, drawing on new research conducted for the UK Energy Resource Centre (UKERC), examines the contemporary public debate on climate change and the linked issue of energy security. It analyses the key processes which affect the formation of public attitudes and understanding in these areas, while also developing a completely new method for analysing these processes. The authors address fundamental questions about how to adequately inform the public and develop policy in areas of great social importance when public distrust of politicians is so widespread. The new methods of attitudinal research pioneered here combined with the attention to climate change have application and resonance beyond the UK and indeed carry global import"--
Includes bibliographical references and index.
Keywords: Climatic changes -- Social aspects